Research on Failure Characteristics of Concrete Three-Point Bending Beams with Preexisting Cracks in Different Positions Based on Numerical Simulation - Liuqun Zhao (Hindawi-Wiley, 2021)
Concrete three-point bending beams with preexisting cracks are widely used to study the growth process of I-II mixed mode cracks. Studying the failure characteristics of preexisting cracks at different locations on concrete three-point bending beams not only has important scientific significance but also has a wide range of engineering application backgrounds in the safety assessment of engineering structures. In this paper, through several numerical experiments, the influence of preexisting cracks at different positions on the failure characteristics of concrete three-point bending beams is studied, and three typical failure modes are obtained. The failure process of the specimens with three typical failure modes is discussed in detail, and it is pointed out that the crack failure mode is tensile failure. The change trends of bearing capacity, acoustic emission quantity, and acoustic emission energy of three typical failure modes are analyzed. The maximum bearing capacity, the maximum acoustic emission quantity, and energy of three failure modes of concrete three-point bending beams generally show an increasing trend.